(untitled) (Bangladesh Journal of Botany, 2012)
Seasonal variation on bacterial load irrespective of heterotrophic and enteric bacteria was noticed in Gulshan lack of Dhaka Metropolitan city. The lowest number (1.56×106 cfu/100 ml) in the summer and the highest (19.03×106 cfu/100 ml) were recorded during winter. Among the isolated bacteria 32 were studied in details and provisionally identified as Bacillus cereus (1), B. sphaericus (1), B. subtilis (1), B. brevis (2), B. pasteuri (1), B. stearothermophilus (1), B. azotoformans (1), B. pantothenticus (1), B. licheniformis (1), B. circulans (1), B. insolitus (1), Planococcus citrius (1), Micrococcus sedentarius (1), Pseudomonas. syringae (4), P. aeruginosa (1), P. cichorii (1), Escherichia (2), Klebsiella (1), Aeromonas (1), Proteus (1), Enterobacter (1), Salmonella (2), Yersinia (1), Shigella (1), Hafnia (1), and Alcaligens (1). The temperature and pH of the water samples varied between 24.3 and 29.2º C and 6.54 and 7.12, respectively. Chemical contents (mg/l) like NH4 +-N, NO3 –N and phosphorus ranged 3.06 (Winter) to 14.86 (Summer), 0.32 (in Rainy season) to 13.02 (Summer) and 0.81 (Rainy season) to 1.86 (Summer), respectively. The enteric bacterial load (0.03 × 105 cfu/100 ml in Rainy season to 21.2 × 105 cfu/100 ml in Winter) and the presence of Escherichia, Aeromonas, Enterobacter, Pseudonomas in the samples indicated significant level of microbial pollution of the lake. Key words: Aerobic-heterotrophic; Bacteria; Enteric bacteria; Chemical factors DOI: http://dx.doi.org/10.3329/bjb.v40i2.9753 Bangladesh J. Bot. 40(2): 105-111, 2011 (December)